Altered Primary Motor Cortex Neuronal Activity in a Rat Model of Harmaline-Induced Tremor During Thalamic Deep Brain Stimulation - Lee, Jihyun; Chang, Su-youne (Frontiers in Cellular Neuroscience, 2019)
Although deep brain stimulation (DBS) is clinically effective surgical treatment for essential tremor (ET), its neurophysiological mechanisms are not fully understood. Since the ventrolateral (VL) thalamus is the most popular DBS target for ET and it is known that thalamic nucleus plays a key role in relaying information about the external environment to the cerebral cortex, it is important to investigate mechanisms of thalamic DBS in the context of cerebello-thalamo-cortical neuronal network. To examine this, we measured single-unit neuronal activities in the resting state in M1 during VL thalamic DBS in the harmaline-induced tremor rats and analyzed neuronal activity patterns in the thalamo-cortical circuit. Four activity patterns, such as oscillatory burst, oscillatory non-burst, irregular burst and irregular non-burst, were identified by harmaline administration and those firing patterns were differentially affected by VL thalamic DBS, which seems to drive pathologic cortical signals to signals in normal status. Since specific neuronal firing patterns like oscillation or burst are considered important for information processing, our results suggest that VL thalamic DBS may modify pathophysiologic relay information rather than simply inhibit the information transmission.